Production of heterogeneous catalysts for biodiesel synthesis - beenish, shah; Sulaiman, Sarina; Jamal, Parveen; Alam, Md Zahangir (World Academy of Research and Publication, 2014)
The waste food material namely crab shell, egg shell and fish bone is screened for biodiesel synthesis by trans - esterification reaction to determine the source providing the highest biodiesel yield. The soli d oxide materials were calcined at 900°C for 2 - 4 hrs to convert CaCO 3 to CaO species. Trans - esterification is carried out at 65°C for 4 hrs with varied methanol to oil ratio. It was found that although egg shell, and crab shell gave average biodiesel yield s, fish bone provided outstanding results of the three catalysts. This research signifies successful application of waste resources as an emerging prospective for economical preparation of heterogeneous catalyst, developing an unconventional avenue for reusing of this solid waste.